Prehabilitation in patients undergoing colorectal surgery fails to confer reduction in overall morbidity: Results of a single-center, single-blinded, randomized controlled trial. (28th May 2021) - Gloor, S; Misirlic, M; Frei-Lanter, C; Herzog, P; Müller, P; Schäfli-Thurnherr, J; Schregel, D; Lamdark, T; Wyss, R; Unger, I; Gisi, D; Greco, N; et al.
Abstract: Objective: Patients undergoing major surgery are prone to a functional decline due to the impairment of muscle, cardiorespiratory and neurological function as a response to surgical stress. Currently, there are solely weak recommendations in the ERAS protocol regarding the role of preoperative physical activity and prehabilitation in patients undergoing colorectal surgery. Studies in heterogenous cohorts showed contradictory results regarding the impact of prehabilitation on the reduction of postoperative complications. This randomized controlled trial assesses the impact of prehabilitation on postoperative complications in patients undergoing colorectal surgery within an ERAS protocol. Methods: Between July 2016 and June 2019, a single-center, single-blinded, randomized controlled trial designed to test whether physiotherapeutic prehabilitation vs. normal physical activities prior to colorectal surgery may decrease morbidity within a stringent ERAS protocol was carried out. The primary endpoint was postoperative complications assessed by Comprehensive Complications Index (CCI®). Primary and secondary endpoints for both groups were analyzed and compared. Results: A total of 107 patients (54 in the pERACS and 53 in the control cohort) were included in the study and randomized. Dropout rate was 4.5% (n = 5). Mean age (SD) in the control cohort was 65 (29–86) and 66 (24–90) years in pERACS cohort. The pERACS cohort contained more female patients (40% vs. 55%, p = 0.123) and a higher percentage of colorectal adenocarcinoma (32% vs. 23%, p = 0.384) although not significant. Almost all patients underwent minimally invasive surgery in both cohorts (96% vs 98%, p = 1.000). There was no between-cohort difference in the primary outcome measure 30-day Comprehensive Complications Index (15 [0 – 49] vs. 18 [0 – 43], p = 0.059). Secondary outcome as complications assessed according to Clavien-Dindo, length of hospital stay, reoperation rate and mortality showed no difference between both cohorts. Conclusion: Routine physiotherapeutic prehabilitation cannot be recommended for patients undergoing colorectal surgery within an ERAS protocol (Grade A recommendation). To eliminate other confounders like geographical difference or difference in surgical technique, further multicenter RCTs are needed.